Developmental regulation of Lck targeting to the CD8 coreceptor controls signaling in naive and memory T cells. - Bachmann, M; Gallimore, A; Linkert, S; Cerundolo, V; Lanzavecchia, A; Kopf, M; Viola, A (1999)
The question of whether enhanced memory T cell responses are simply due to an increased frequency of specific cells or also to an improved response at the single cell level is widely debated. In this study, we analyzed T cell receptor (TCR) transgenic memory T cells and bona fide memory T cells isolated from virally infected normal mice using the tetramer technology. We found that memory T cells are qualitatively different from naive T cells due to a developmentally regulated rearrangement of the topology of the signaling machinery. In naive cytotoxic T cells, only a few CD8 molecules are associated with Lck and the kinase is homogeneously distributed inside the cell. However, in vivo priming of naive T cells induces the targeting of Lck to the CD8 coreceptor in the cell membrane and the consequent organization of a more efficient TCR signaling machinery in effector and memory cells.